A Review of Psychology in the Astronomical Thought of Shaykh Abdullah Fahim - Zainal Badri, Khairul Nizam Bin (Jurnal Sains Sosio Humaniora, 2023)
Astronomy is a very important field because its use covers the entire daily activities of human beings. With the knowledge of astronomy, humans can plan activities well. This study seeks to examine the philosophy of astronomy in the thought of Shaykh Abdullah Fahim (1869 - 1961 AD), a prominent scholar of Penang and its impact on life. Shaykh Abdullah Fahim received his education in astronomy and other religious sciences in Makkah and Madinah. He also took the Naqsyabandiyyah tariqat from his teacher Sayyid Muhammad Amin bin Ahmad Al-Madani. In terms of his educational background, it is almost the same as the Indonesian Minangkabau scholar, Shaykh Muhammad Jamil Jambek bin Saleh Datuak Maleka (1862 - 1947) who has skills in astronomy, and a practitioner of the Naqsyabandiyyah tariqah. On the other hand, this study seeks to look at the significance of this field of astronomy to human psychology according to his point of view. This qualitative -based study uses a fully library approach to gather as much information about Shaykh Abdullah Fahim especially in the field of astronomy. Cross reference is made to the figures of the contemporary Malay scholars to obtain further information about the figures involved in teaching astronomy. In the context of psychology, the field of astronomy is not only able to trigger a high level of thinking but at the same time able to provide motivation and inspiration to humans to start an activity in daily life.